A busca pela eficiência legislativa no combate à corrupção em empresas: análise da legislação anticorrupção brasileira, inglesa e norte-americana - Reis, Marianne Yumi Sato Felix (2021)
With regard to corruption, we tend to relate it to the public sector. Not surprisingly, since there are in fact a large number of media cases involving public officials in activities that have caused real damage to our society. However, corruption also occurs in the corporate environment and is a long-standing and recurring problem in private organizations. In this scenario, the creation of laws that fight not only corruption, but corruption in the business sphere became necessary and, therefore, three laws stand out in this struggle: the North American Foreign Corrupt Practices Act (FCPA) of 1977, the British Law UK Bribery Act of 2011 and Law n. 12.846/2013, also known as the Brazilian Anti-Corruption Law. These are mechanisms created to hold companies accountable for engaging in corrupt acts. Nevertheless, many companies continue to fail to comply with legal provisions and the corruption generated in the corporate environment by people they belong to remains an obstacle in business activity. Therefore, in this work, we will analyze the provisions and the application of these laws, while we will also analyze measures that further strengthen compliance with these mechanisms, so that the fight against corruption is more likely to be victorious in the near future